Bamboo Dome: Tradition meets Digital Manufacturing - Berna Abanoz; Gregor Grunwald; Vasanth K. Bhat; Sudhir Acharya (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This study describes the design and construction process of a bamboo dome structure within the framework of an Indo-German international project. The design of the dome developed in collaboration with a group of students. Each student creates a design idea for each of the triangles on the dome with a specific design idea and connection details. The design aims to demonstrate how bamboo material can be designed using digital manufacturing techniques as well as constructed using traditional connection methods. The aim of the design build project is not only to construct a bamboo dome, but also to investigate how bamboo can be integrated with modern manufacturing techniques.  In the design, specific connectors and surfaces are planned to be produced using digital fabrication tools that will be integrated into the dome design. Therefore, this research, aims to provide a model for sustainable and innovative building systems by investigating the integration of bamboo with digital fabrication.